GENETIC ANALYSIS OF SEED MORPHOMETRIC OF YELLOW KERNEL SINGLE CROSS HYBRID MAIZE - D.J., OGUNNIYAN; J.O., OLASOJI; K.O.S., ADERIYE (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2021)
Seed dimension improvement requires an assessment of seed metrics and the relationships among the seed traits. Therefore, the objectives of this study were to detect the basic principles underlying seed shape in maize, determine the relationships among the elements of the seed dimension and examine heterosis in the seed morpho-traits. Seeds of 50 yellow kernel single cross hybrid maize were subjected to morphometric analysis in three replications along with their parents in a laboratory experiment using digital imaging system. Data on seed angle (SA), seed embryo angle (SEA), seed diameter (SD), seed perimeter (SP), seed thickness (ST), seed width (SW) and seed length (SL) were collected while seed area (SAR), seed shape factor (SSF), flatness index (FI) and eccentric index (SI) were estimated. The data were subjected to variance and Pearson’s correlation analyses. Heterosis was estimated for the seed morpho-traits and index score method was employed to rank the hybrids for heterosis. High significant variation existed for the seed morpho-traits among the hybrids. Seed diameter, seed perimeter, seed width, seed length and seed area distinguished and rated TZEI13×BD74-161, BD74-165×BD74-161, TZEI124×BD74-161 and TZEI146×BD74-161 high in seed morphometric. Seed angle correlated with the SEA; the SD associated with SP, SL, SW, SAR and SSF whereas SP can be selected for SSF and flatness index. The SD, SW and SL can be improved through heterosis. The crosses involving inbred lines TZEI13 and BD74-161 expressed high vigour over their parents. Hence, they can be explored in hybrid maize seed production.